DIPLOMASI PUBLIK INDONESIA DALAM MEMPROMOSIKAN PARIWISATA INDONESIA MELALUI FESTIVAL BEKUO BONO 2018-2019 - Monica Ilhami; Den Yealta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study analyzes public diplomacy efforts undertaken by local governments, provincial governments and the central government in bringing Indonesian tourism to be known through the 2018-2019 Bekudo Bono Festival. Bono which is a rare event or tidal bore is an international surfing tourism potential that is developing in the village of Teluk Meranti, Pelalawan Regency, Riau Province. This phenomenon shows a rare event, where large waves with a height of 2-6 meters become a tourism opportunity in the field of surfing. This case is analyzed in the State level and Pluralism Perspective with Tourism Theory and the concept of Public Diplomacy. In this case, public diplomacy carried out by local, provincial and central government actors has become a tool to introduce Bono tourism through promotions carried out both at home and abroad. This effort also has an important role in international politics which is included in the practice of diplomacy. Public Diplomacy is a form of effort in changing the perspective of other people towards a country, where the scope is the public. This diplomacy is one way and enters into the soft power section to gain other advantages. Indonesia has abundant natural wealth, especially tourism, this requires public diplomacy to promote this potential to the international community, with the aim of gaining international recognition and certification in increasing tourist visits and promoting Indonesia's excellence. Therefore, through various efforts included in the public diplomacy section involving various actors and utilizing electronic media to promote the uniqueness of the Bono waves to the world. Keywords: Tidal bore, Bono Waves, Public Diplomacy, Tourism.